Hygiene and sanitation public health risks in illicit alcohol production and retail in Zambia - Mukupa, Musawa; Zyambo, Cosmas; Phiri, Masauso Moses; Zulu, Richard; Matenga, Tulani Francis L.; Mabanti, Kumbulani; Hainze, Anna; Ogwell, Ahmed; DeJong, William; Menda, Dhally M.; Rizzo, Angela; Goma, Fastone; et al. (Frontiers in Epidemiology, 2025)
IntroductionIllicit alcohol, existing outside legal frameworks, lacks safety standards and may contain harmful substances. In Africa, the illicit alcohol market is pervasive, contributing to significant public health challenges. The state in Zambia may not be so different where abuse of alcohol was associated to unintended injuries, suicidal ideation and physical fights that in some cases lead to death. This mirrors these challenges; according to the Zambia Stepwise Survey for Non-Communicable Diseases (NCDs) Risk Factors (2017), 21.7% of adults consume alcohol, with urban areas experiencing higher rates of illicit production.AimThe study aimed to assess the public health risk implications associated with the production and retail of illicit alcohol based on the hygiene and sanitation of these premises. A quantitative approach was employed in Livingstone, Lusaka, and Ndola.MethodsWe employed a quantitative approach was conducted in Livingstone, Lusaka, and Ndola. A hygiene and sanitation observation tool obtained from the Lusaka City Council was adapted and utilized to evaluate the conditions of these premises.ResultsThe study found that Livingstone exhibited the highest rate of unavailability of water supply at illicit alcohol production sites, with 18% lacking access to water, while Lusaka had 13% without water supply of the zones selected, all sites in Ndola had water supply.ConclusionGiven the growing trend of consuming illicit alcohol in such unsanitary environments, urgent interventions are warranted. The study recommends the implementation of enforcement of regulations, including regular inspections and enhanced enforcement mechanisms, to ensure hygienic and sanitary production practices.